A laboratory and field evaluation of Macrocyclops distinctus, Megacyclops viridis and Mesocyclops pehpeiensis as control agents of the dengue vector Aedes albopictus in a peridomestic area in Nagasaki, Japan - Dieng, Hamady; Boots, M.; Tuno, N.; Tsuda, Y.; Takagi, M. (The Royal Entomological Society, 2002)
The use of the cyclopoid copepods Macrocyclops distinctus (Richard)Megacyclops viridis (Jurine) and Mesocyclops pehpeiensis Hu (Cyclopoida: Cyclo-pidae) as biological control agents against the dengue vector Aedes albopictus(Skuse) (Diptera: Culicidae) was evaluated. In the laboratory their predatoryability was highest against the younger instars of Ae. albopictus and none of thethree copepods killed the fourth instar. Except for M. viridis, predatory ability wasaffected by the size of the container: the smaller the container, the higher thepredation. A 4-month field test was conducted to examine the impact of thesepredators on wild Ae. albopictus. Thirty artificial containers were placed in aperidomestic area to allow Ae. albopictus colonization. We showed continuousand similar oviposition responses in treated and control containers. The densitiesof Ae. albopictus showed considerable short-term changes and were much reducedby the copepod species. Macrocyclops and the mixture of all three provided betterAe. albopictus control than either Megacyclops or Mesocyclops alone. When larvaldensities peaked in the control containers in August and September, the overallreduction due to the copepods was nearly complete. Mesocyclops inoculated alonehad the highest population survival. However, the growth and survival of all thecopepod species was poor when the three genera were mixed. Based on theirperformance and survival in the trial, Macrocyclops and Mesocyclops meritconsideration as bio-control agents of Ae. albopictus.